PENGARUH KEPEMIMPINAN VISIONER KEPALA SEKOLAH TERHADAP MOTIVASI KERJA GURU DI SMA NEGERI 1 PANOMBEIAN PANE PEMATANGSIANTAR - Jon Roi Tua Purba; Adrianus Th Mahulae; Deasy Manurung; Lustani Samosir (Smart Education, 2026)
Abstract: This study aims to analyze the influence of principals’ visionary leadership on teachers’ work motivation at SMA Negeri 1 Panombeian Pane Pematangsiantar. The study employed a quantitative approach with a survey design. The population consisted of all teachers at SMA Negeri 1 Panombeian Pane Pematangsiantar who participated as research respondents. Data were collected using a Likert-scale questionnaire developed based on the indicators of visionary leadership and teachers’ work motivation. The data were analyzed using descriptive statistics and simple linear regression with the assistance of SPSS software. The results revealed that principals’ visionary leadership was categorized as high with a mean score of 4.12 (82.5%), while teachers’ work motivation was also categorized as high with a mean score of 4.05 (81.0%). The simple linear regression analysis indicated that principals’ visionary leadership had a positive and significant effect on teachers’ work motivation, with a t-value of 5.167 and a significance value of 0.000 (p < 0.05). The coefficient of determination (R²) of 0.412 indicated that principals’ visionary leadership contributed 41.2% to teachers’ work motivation, while the remaining 58.8% was influenced by other factors not examined in this study. These findings suggest that better implementation of visionary leadership by school principals is associated with higher levels of teachers’ work motivation. Therefore, strengthening principals’ visionary leadership competencies is essential for enhancing teachers’ motivation and improving educational quality. Keywords: visionary leadership, principal, teachers’ work motivation, educational leadership, educational management. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh kepemimpinan visioner kepala sekolah terhadap motivasi kerja guru di SMA Negeri 1 Panombeian Pane Pematangsiantar. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei. Populasi terdiri dari seluruh guru di SMA Negeri 1 Panombeian Pane Pematangsiantar yang berpartisipasi sebagai responden penelitian. Data dikumpulkan menggunakan kuesioner skala Likert yang dikembangkan berdasarkan indikator kepemimpinan visioner dan motivasi kerja guru. Data dianalisis menggunakan statistik deskriptif dan regresi linier sederhana dengan bantuan perangkat lunak SPSS. Hasil penelitian menunjukkan bahwa kepemimpinan visioner kepala sekolah dikategorikan tinggi dengan skor rata-rata 4,12 (82,5%), sedangkan motivasi kerja guru juga dikategorikan tinggi dengan skor rata-rata 4,05 (81,0%). Analisis regresi linier sederhana menunjukkan bahwa kepemimpinan visioner kepala sekolah memiliki pengaruh positif dan signifikan terhadap motivasi kerja guru, dengan nilai t sebesar 5,167 dan nilai signifikansi 0,000 (p < 0,05). Koefisien determinasi (R²) sebesar 0,412 menunjukkan bahwa kepemimpinan visioner kepala sekolah berkontribusi sebesar 41,2% terhadap motivasi kerja guru, sedangkan sisanya sebesar 58,8% dipengaruhi oleh faktor-faktor lain yang tidak diteliti dalam studi ini. Temuan ini menunjukkan bahwa implementasi kepemimpinan visioner yang lebih baik oleh kepala sekolah dikaitkan dengan tingkat motivasi kerja guru yang lebih tinggi. Oleh karena itu, penguatan kompetensi kepemimpinan visioner kepala sekolah sangat penting untuk meningkatkan motivasi guru dan meningkatkan kualitas pendidikan. Kata kunci: kepemimpinan visioner, kepala sekolah, motivasi kerja guru, kepemimpinan pendidikan, manajemen pendidikan